Perancangan Mesin Pengerol Pipa dengan Sistem Kerja otomatis dan Manual - Abd.Kadir; Aminur (Program Pendidikan Vokasi Teknik Mesin, 2021)
The concept of Designing the Tools of Pipe Rolling Machines With Automatic and Manual Work Systems reflects on the design by means of several stages, including projeck definition, project preparation, product technical specifications, product concept planning, product design, to documents for manufacturing products. The next process is analyzing the needs of attention to consideration of planning requirements. Results from the Custom-Designed Tool of Pipe Rolling Machine used to accomplish automatic and manual harverting results: (1) making tool/machine with an efficient worksystem in automatic or manual: (2) The design of the tool or machine with this automatic and manual working system.